Spatially coherent high-order harmonics generated at optimal high gas pressure with high-intensity one- or two-color laser pulses - Jin, Cheng; Lin, Chii D. (My University, 2016)
We investigate the gas-pressure dependence of macroscopic harmonic spectra generated in a high-ionization medium using intense 800-nm laser pulses. The harmonics obtained at the optimal pressure show good spatial coherence with small divergence (less than 2 mrad) in the far field. By analyzing the evolution of the laser's electric field as it propagates, we find that dynamic phase matching conditions are fulfilled in the second half of the gas cell and that harmonic yields do not depend on the position of the gas cell with respect to the focusing position. We also demonstrate that harmonic yields at the optimal pressure can be further enhanced by increasing input laser energy or by adding a few percent of second or third harmonic to the fundamental.
Citation: Jin, C., & Lin, C. D. (2016). Spatially coherent high-order harmonics generated at optimal high gas pressure with high-intensity one- or two-color laser pulses. Physical Review A, 94(4), 6. doi:10.1103/PhysRevA.94.043804
Keywords: Water-Window Region; X-Ray; Attosecond Pulses; Nonlinear Optics; Soft; Field